2015
DOI: 10.4081/cp.2015.733
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Pituitary Mass Revealing a Primary Hypothyroidism!

Abstract: Autoimmune hypothyroidism is a common medical condition. Its revelation by thyrotrophic hyperplasia is an unusual and may be misdiagnosed as a pituitary adenoma. A 35-year-old man is referred to us for endocrinological assessment before surgery of a pituitary macroadenoma with bitemporal hemianopsia. Biological data reveal profound primary hypothyroidism. With thyroid hormone substitution, the thyroid function was normalized. Follow-up magnetic resonance imaging, showed the complete shrinkage of the pituitary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Increase in Thyrotrophic cells is a phenomenon seen is protracted case of Hypothyroidism and may present with features consistent with pituitary macroadenoma [8]. The mechanism which causes increase In numbers of Thyrotrophic cells is through the negative feedback loop; decrease in levels of circulating thyroid hormones causes the thyrotrophin releasing hormones (TRH) to overstimulate the thyrotrophs [8].…”
Section: Discussionmentioning
confidence: 99%
“…Increase in Thyrotrophic cells is a phenomenon seen is protracted case of Hypothyroidism and may present with features consistent with pituitary macroadenoma [8]. The mechanism which causes increase In numbers of Thyrotrophic cells is through the negative feedback loop; decrease in levels of circulating thyroid hormones causes the thyrotrophin releasing hormones (TRH) to overstimulate the thyrotrophs [8].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous similar clinical cases have also been published, but with reportedly lower prolactin levels (below 100 ng/ml). 14,15 Vitiligo is relatively common (prevalence of 0.5-2.0% of the general population), but its pathogenesis is not fully understood. Autoimmunity as an etiological cause has been suggested because of the frequent association with other autoimmune diseases, with autoimmune thyroid disease present in 14 to 34% of vitiligo cases.…”
Section: Discussionmentioning
confidence: 99%
“…Long-standing primary hypothyroidism in children with high serum levels of thyroid-stimulating hormone (TSH), and the subsequent proliferation of TSH-releasing cells, may lead to pituitary hyperplasia, causing what is known as pituitary hyperplasia secondary to primary hypothyroidism (PHPH) [ 1 ]. PHPH was first reported in adults by Niepce in 1851, with similar cases reported thereafter [ 3 5 ]. However, PHPH is rarely reported in children; a recent review identified only 18 cases of pediatric PHPH in the literature [ 1 ].…”
Section: Introductionmentioning
confidence: 92%